Mutagenic effects of allylisothiocyanate in Escherichia coli WP 67 - Ríhová, E (Folia microbiologica, 1982)
A mutagenic effect of allylisothiocyanate (AITC) on E. coli WP 67 (trp uvrA polA) was only found in a test with metabolic activation in vitro. Mixed function oxidases containing cytochrome P-450 are not responsible for the conversion of AITC to mutagenic products. Liver microsomal fractions of rat, mouse, chinese hamster, goat and monkey were used for in vitro metabolic activation. The mutagenic effect of AITC differed in individual animal species according to the protein content in the microsomal fraction. Allylamine (formed by hydrolysis of AITC) did not exhibit any mutagenic effect.
Keywords: Chlorocebus aethiops; Mutagenicity Tests; jaterní mikrozomy; křečci praví; Microsomes, Liver; techniky in vitro; Thiocyanates; isothiokyanatany; kozy; Female; Rats, Inbred Strains; thiokyanatany; Escherichia coli; krysa rodu Rattus; Mutagens; zvířata; Enzyme Activation; myši; Mice; Cricetulus; Cercopithecus aethiops; testy genotoxicity; ženské pohlaví; Male; Isothiocyanates; Goats; In Vitro Techniques; Cricetinae; Rats; Animals; aktivace enzymů; mutageny; mužské pohlaví; inbrední kmeny potkanů